1989
DOI: 10.1042/bst0170572
|View full text |Cite
|
Sign up to set email alerts
|

Methylmalonate increases glucose uptake in vitro by brain of young rats

Abstract: Methylmalonic acidaemia is an inherited metabolic disorder generally associated with severe clinical features. Those who survive the first months present a variable degree of mental retardation (Rosemberg, 1983). Methylmalonate (MMA) is the major metabolite which accumulates in tissues of methylmalonic acidaemic patients. To our knowledge, only two studies have been done on the effects of MMA on brain metabolism (Frenkel et a/., 1973; Patel et a/., 1976). Since glucose is the major substrate that throughout li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…Therefore, it appears that more pyruvate is diverted to lactate instead of being oxidized in the Krebs cycle. This is in agreement with our previous findings showing that MMA inhibits brain succinate dehydrogenase activity in a dose-response way (Dutra et al, 1989).…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, it appears that more pyruvate is diverted to lactate instead of being oxidized in the Krebs cycle. This is in agreement with our previous findings showing that MMA inhibits brain succinate dehydrogenase activity in a dose-response way (Dutra et al, 1989).…”
Section: Methodssupporting
confidence: 93%
“…We therefore assume that brain lactate release in our assay represents lactate production. Total brain glucose uptake also increased with MMA concentrations in the incubation medium (F(3,28) = 2.215, p < 0.05) (Table 1) in a dose-dependent pattern (regression coefficient 0.774, p < 0.05), thus confirming our previous findings (Dutra et al, 1989(Dutra et al, , 1991. The table also shows that lactate production was proportional to glucose utilization, leading one to speculate that the increment in brain glucose uptake caused by MMA was mainly diverted to lactate.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…We recently found that MMA inhibits succinate dehydrogenase (SDH) activity in brain of young rats (Dutra et al 1989). In addition, we also demonstrated that MMA diminishes fl-hydroxybutyrate (BHB) but not acetoacetate incorporation into brain prisms of suckling rats, owing to inhibition of fl-hydroxybutyrate dehydrogenase (HBDH) (EC.I.I.I.30) activity (Dutra et al 1991).…”
Section: Durra Et Almentioning
confidence: 94%
“…Those who survive present with a variable degree of physical and mental retardation (Rosenberg and Fenton 1989).Various metabolic effects have been attributed to MMA and methylmalonyl-CoA. We have previously found important effects of MMA on brain metabolism (Wajner et al 1982(Wajner et al , 1988Dutra et al 1989Dutra et al , 1991.…”
mentioning
confidence: 99%